Democracy Promotion as Foreign Policy Temporal othering in international relations - Elliott, Cathy (Taylor & Francis, 2016)
Democracy Promotion as Foreign Policy looks at democracy promotion as a form of foreign policy. It asks why democracy was seen to be the answer to the 7/7 bombings and why it should be promoted not in Britain, but in Pakistan. The logic and the modes of thinking that drove this response are examined through analysis of the narratives of time, history, development, civilisation and the ineluctable spread of democracy.